Multiple spark plugs coupled with pressure sensors: A new approach for knock mechanism study on SI engines. (15th July 2021) - Shi, Hao; Uddeen, Kalim; An, Yanzhao; Pei, Yiqiang; Johansson, Bengt
Abstract: Controlled knock combustion is the focus of academic and industrial research for modern spark-ignition engines to achieve higher thermal efficiency and better performance. To understand the knock formation mechanism, a refitted compression-ignition engine equipping with a port fuel injection system was operated under spark-ignition conditions. A customized liner with four side spark plugs was used to trigger controllable knock, through various spark strategies (e.g., spark number, timing, and location). Four side pressure sensors and a top sensor mounted on the cylinder head were used to record the knock pressure oscillation. Fast Fourier transform and wavelet analysis were performed to evaluate the frequency of pressure oscillations. The results showed that activating more spark plugs could promote knock propensity and intensity along with earlier CA50, but the knock was effectively suppressed when symmetrically activating four spark plugs simultaneously, indicating the fast flame propagation could suppress the knock occurrence. When triggering 2 or 3 spark plugs simultaneously, the in-cylinder pressure oscillations display very concentrated directionality among all the knocking cycles, indicating the distributing tendency of hot spots in these cases. With the activated spark plug number ranging from 1 to 3, the acoustic resonance focused on (1, 0) mode, while the four activated spark ignition led to higher (0, 1) mode, indicating the auto-ignition initiated close to the chamber center. Compared with the side sensors, the top sensor could recognize more resonance modes. Similar time ranges of frequency bands with fixed CA50 were noted for all spark plug numbers. Higher frequency signal decayed faster than lower during the knocking vibrations. As expected, we find that auto-ignition starts earlier when advancing the spark timing. Thereby more energy is released by knock, which explains the knock amplitude growth with earlier spark timing. Highlights: Multiple spark ignition system was designed to study the controllable knock combustion. A fast flame propagation method was proposed to suppress and control the knock occurrence. Knock vibration frequencies and directions in space and time domains were investigated. Effects of different spark strategies on knock propensity and intensity were discussed. Acoustic resonance modes were studied to assess the in-cylinder hot spot distributions.